The Berlin Bourse in the London mirror: An asymmetric comparison of microstructures and the role of Germany's large banks in securities trading, c. 1860-1914 - Michael Buchner (IBF - Institut für Bank- und Finanzgeschichte, 2018)
This article provides the first in-depth account on the organisational history of the Berlin Bourse based on archival evidence. It demonstrates that the microstructures of the Berlin Bourse basically corresponded to the needs and activities of the largest commercial banks and, consequently, argues that these large banks played a 'gatekeeping' role in securities trading. Moreover, the Berlin example perfectly illustrates the close ties which existed between banks and financial markets and the resulting amalgamation of banking and stock-broking activities in imperial Germany. The comparison to the London Stock Exchange also shows that both stock exchanges fulfilled different economic roles within the overall financial system.
Keywords: N20; N23; 330